Reduction of specific energy consumption (SEC) in cement factories through FMEA and energy management - Muktar, Ridwan; Pratoto, Adjar (Jurnal Teknika, 2023)
The cement industry is one of the energy-intensive industries with energy costs reaching 35% - 50% of the total production costs. The main energy sources in cement plants are coal and electricity. Energy use performance can be seen from the specific energy consumption (SEC) of the factory concerned. This paper discusses the possibility of decreasing SEC in a cement production unit with a capacity of 7800 tons per day. The plant operates using a dry process with a calciner and a 4-stage cyclone preheater. The study focuses on three process lines, namely the raw mill process, the kiln & coal mill process, and the finish mill process. The results of the energy audit showed that the performance of the raw mill process line is still close to the design price. Meanwhile, for the kiln & coal mill process line and the finish mill process line, the performance is below the design price. The Failure Mode Effect Analysis (FMEA) method is used to analyze the causes of the high SEC value of each process series. Based on the results of the FMEA, recommendations are given to reduce SEC, and the potential for SEC reduction is estimated at 14.93 kWh/ton of cement.